Product Quality Influence on Corporate Reputation: Evidence from Retail Firms in Nigeria (UNIZIK Journal of Marketing, 2024)
In today’s retail business, the quality of a product can significantly impact a company's corporate reputation, as customers often associate product quality with the overall reputation of retail firms. This study examines the influence of product quality on corporate reputation, with evidence from retail firms in Nigeria. A quantitative research design was employed, focusing on customers of selected retail companies in Lagos State, namely Shoprite, Buyrite, and Spar. A survey method using questionnaires was utilized to collect primary data. The sample size was determined to be 246, and multistage sampling techniques were employed. Of the 246 distributed questionnaires, 150 were retrieved and coded for analysis. Standard multiple regression was used to analyze the data. The results indicate that product quality significantly influences corporate reputation in store-based retail outlets in Lagos State. The study concludes that well-designed quality products that satisfy customer needs, serve their intended purpose, and meet industry standards effectively build trust and sustain corporate reputation. It recommends that retail service providers establish a sustainable corporate reputation through high-quality products to enhance customer confidence and trust. The underlying premise is that higher perceived product quality leads to increased customer patronage.
Keywords: Corporate Reputation; Customer Trust; Product Quality; Quantitative Research; Retail Firms